2005
DOI: 10.1186/1471-2334-5-10
|View full text |Cite
|
Sign up to set email alerts
|

Emergency vaccination of rabies under limited resources – combating or containing?

Abstract: Background: Rabies is the most important viral zoonosis from a global perspective. Worldwide efforts to combat the disease by oral vaccination of reservoirs have managed to eradicate wildlife rabies in large areas of central Europe and North-America. Thus, repeated vaccination has been discontinued recently on a geographical scale. However, as rabies has not yet been eradicated globally, a serious risk of re-introduction remains. What is the best spatial design for an emergency vaccination program -particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…For example, for a spring density of three foxes, the average dispersal distance resulting from the algorithm corresponds to about 14·4 km (median 11·5 km). In comparison with the literature (Jensen 1973), the reported pattern of cumulative distance distribution re‐emerged from the model algorithm (Eisinger et al . 2005).…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, for a spring density of three foxes, the average dispersal distance resulting from the algorithm corresponds to about 14·4 km (median 11·5 km). In comparison with the literature (Jensen 1973), the reported pattern of cumulative distance distribution re‐emerged from the model algorithm (Eisinger et al . 2005).…”
Section: Methodsmentioning
confidence: 67%
“…Additionally, the model was applied successfully to different aspects of large‐scale vaccination programmes and post‐vaccination emergency planning (Thulke et al . 2000; Eisinger et al . 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, spatial disease models have demonstrated that strategic application can be just as effective as uniform application of control measures (e.g., Haydon et al., ; Shaman, ). For example, non‐uniform application of oral rabies vaccine has been explored by several spatial models and found to be a potentially effective way to reduce the 70% threshold standard that is commonly used for vaccination programs (Bohrer, Shem‐Tov, Summer, Or, & Saltz, ; Eisinger, Thulke, Selhorst, & Müller, ; Russell, Real, & Smith, ; Thulke & Eisinger, ). These are important insights because targeted control measures could increase the benefit–cost ratio of management strategies (Eisinger & Thulke, ).…”
Section: Questions That Spatial Models Have Been Used To Answermentioning
confidence: 99%
“…Certainly, culling of TM would probably never be recommended to enhance rabies management, but the culling of reservoir hosts that share or link with habitats of TM may afford greater effectiveness and the timely establishment of non-infectious animals near TM (Eisinger et al, 2005). Recent rabies-transmission models and empirical data indicate that some culling or contraception of reservoir host animals should be considered in management strategies to enhance the effectiveness of ORV or contraception methods, and possibly to protect ''enclaves'' of TM from the virus carried by non-TM Smith and Cheeseman, 2002).…”
Section: General Implications To Rabies Management For Tmmentioning
confidence: 99%